2007
DOI: 10.1016/j.compscitech.2007.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of van der Waals-based interface cohesive law on carbon nanotube-reinforced composite materials

Abstract: Abstract:The nonlinear cohesive law derived from the weak van der Waals force for carbon nanotube/polymer interfaces is incorporated in present study of CNT-reinforced composites.Carbon nanotubes can indeed improve the mechanical behavior of composite at the small strain, but such improvement disappears at relatively large strain because the completely debonded nanotubes behave like voids in the matrix and may even weaken the composite. The increase of interface adhesion between carbon nanotubes and polymer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…From this relation we obtain ffiffi ffi 2 6 p r is the equilibrium distance between atoms, and e is the bonding energy at the equilibrium distance [12].…”
Section: Resultsmentioning
confidence: 99%
“…From this relation we obtain ffiffi ffi 2 6 p r is the equilibrium distance between atoms, and e is the bonding energy at the equilibrium distance [12].…”
Section: Resultsmentioning
confidence: 99%
“…At very small fraction, the presence of silica slightly increases the composite stiffness due to smaller of the contact formed. When it is slightly added, its effect is more apparent as increasing of the contact formed, even at certain fraction the compressive stength attaining 40.47 MPa is maximum value, that it means that contact occured is also maximum and if the fraction is added again, the silica can not interact effectively with PU/solid waste composite due to maximum contact formed, instead it interact with the neighboring silica that increases the brittleness of composite [7,21,22]. As result the composite strength decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [24] reported that at lower content, silica particles disperse into amine and carbonyl groups of PU. In the silica/PU dispersed, the oxygen of silica interacts with the hydrogen of amine group to form hydrogen interaction that is very important in governing composite strength [21,25].…”
Section: -2mentioning
confidence: 99%
“…Fundamental to the reinforcing effectiveness are the interfacial characteristics between the nanotube and the matrix. Upon this issue, a considerable number of works have been reported previously [11,14]. Since CNTs usually agglomerate due to van der Waals force [16], they are extremely difficult to disperse and align in most of the common polymer matrices [17].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…It was concluded that the shear strength of a polymer/nanotube interface with weak non-bonded interactions could be increased by over an order of magnitude with the introduction of a relatively low density (<1%) of chemical bonds between the nanotube and polymer. Tan et al [11] studied the effect of van der Waals-based interface forces on the CNT-polymer composite. They incorporated a nonlinear cohesive law introduced by Jiang et al [12] in the micromechanical model of the composite.…”
Section: Introductionmentioning
confidence: 99%